2006
DOI: 10.3406/ecmed.2006.1415
|View full text |Cite
|
Sign up to set email alerts
|

Écologie trophique de la Cigogne blanche (Ciconia ciconia) et du Héron garde-boeufs (Bubulcus ibis) en Kabylie (Algérie)

Abstract: Les divers milieux fréquentés par la Cigogne blanche (Ciconia ciconia) de janvier à août 1995 et le Héron garde-boeufs (Bubulcus ibis) de novembre 1994 à octobre 1995 dans la vallée du Sébaou ont été caractérisés par des indices de fréquentation. L’activité de chasse et d’alimentation de ces deux espèces a été suivie par observation directe de mars à juillet 1995, et leurs proies ont été classées en catégories selon les habitats occupés. Une approche quantitative du régime et de l’activité alimentaire (nombre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…However, information on the White Stork diet in Algeria is generally scarce, and mostly highlighted the diet plasticity and its role in the current expansion of the species in the country (Boukhemza, 2001;Moali-Grine, 2007;Djerdali, 2010). Several studies over the Palaearctic have investigated the variation of the species' diet based on environmental variables such as climatic conditions (Jovani and Tella, 2004;Tryjanowski et al, 2009;Chenchouni and Si Bachir, 2014), feeding habits (Mužinić and Rašajski, 1992;Boukhemza et al, 2006), age of the chicks (Djerdali et al, 2008), habitat type (Tsachalidis and Goutner, 2002), seasons and foraging habitat selection (Alonso et al, 1991). Furthermore, results of the key studies on the White Stork diet show that the species is mainly an opportunistic insectivore (Vrezec, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, information on the White Stork diet in Algeria is generally scarce, and mostly highlighted the diet plasticity and its role in the current expansion of the species in the country (Boukhemza, 2001;Moali-Grine, 2007;Djerdali, 2010). Several studies over the Palaearctic have investigated the variation of the species' diet based on environmental variables such as climatic conditions (Jovani and Tella, 2004;Tryjanowski et al, 2009;Chenchouni and Si Bachir, 2014), feeding habits (Mužinić and Rašajski, 1992;Boukhemza et al, 2006), age of the chicks (Djerdali et al, 2008), habitat type (Tsachalidis and Goutner, 2002), seasons and foraging habitat selection (Alonso et al, 1991). Furthermore, results of the key studies on the White Stork diet show that the species is mainly an opportunistic insectivore (Vrezec, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the White Stork attempts to balance the intake of foods high in biomass with foods high in energy (Kosicki et al, 2006), which contributes to its selection of heterogeneous productive habitats (Boukhemza et al, 2006). Other studies highlighted the impact of climate and food variability on reproductive parameters (Tortosa et al, 2003;Tryjanowski et al, 2005;Denac, 2006;Kosicki, 2012;Si Bachir et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study showed that the Cattle Egret can nest at relatively low heights of 4 to 5 m, sometimes less depending on the height and shape of the canopy. Previous studies have reported nests between 8 and 18 m on Phoenix canariensis and Schinus molle in the Hadjout area (Setbel, 2008) and on ash trees in El Kseur (Si Bachir et al, 2000) and over 18 m in Kabylie region on Eucalyptus sempervirens (Boukhemza et al, 2006). In addition to choosing the place for security, in an arid zone of Nigeria, herons have a predilection for thorny trees such as Acacia albida, A.…”
Section: Nest Locationsmentioning
confidence: 98%
“…(Si Bachir et al, 2000), on Eucalyptus sempervirens, Platanus orientalis, Fraxinus angustifolia, Cupressus macrocarpa and Araucaria sp. (Boukhemza et al, 2006).…”
Section: Number Of B Ibis In the Heronrymentioning
confidence: 99%
See 1 more Smart Citation